Exploring the Interconnections of Genetic, Lifestyle, and Epigenetic Influences on Brain Aging: A Comprehensive Review - Mehrabadi, Shima; Barati, Sama (Current Alzheimer Research, 2025)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by progressive cognitive decline and memory loss. The etiology of AD is complex and multifactorial, with contributions from genetic, lifestyle, and environmental factors. Recent advances in genetics, epigenetics, and animal models have shed light on the underlying mechanisms of brain aging and the development of AD, revealing potential targets for therapeutic intervention. In this comprehensive review, we examine the current understanding of the genetic, lifestyle, and epigenetic factors that shape the landscape of brain aging and AD. We discuss recent findings in the field of AD genetics, including the role of the APOE gene, and the potential of novel genome-wide association studies to identify new genetic risk factors. We also review the impact of lifestyle factors, such as diet, exercise, and social engagement, on brain aging and AD, and explore the role of epigenetic mechanisms, such as DNA methylation and histone modifications, in shaping AD risk.
Keywords: Alzheimer' s disease